2018
DOI: 10.1007/s12265-018-9848-3
|View full text |Cite
|
Sign up to set email alerts
|

Release of Mitochondrial and Nuclear DNA During On-Pump Heart Surgery: Kinetics and Relation to Extracellular Vesicles

Abstract: (UiO) in 2015. There I have met many fantastic people whose openness, enthusiasm, and disposition toward risky investments made this work possible. I will first greatly acknowledge Professor Jarle Vaage for inviting me to UiO and being my permanent co-supervisor. Thank you for invaluable help and for sharing your realistic optimism during all these exciting and challenging years. I am especially thankful for introducing me to Professor Guro Valen. Professor Guro Valen was a bright and inspiring supervisor unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 95 publications
2
10
0
Order By: Relevance
“…While the absolute plasma levels of mtDNA during cCPB were comparable with other studies investigating CABG patients, the kinetics differed from some studies [ 17 , 18 ]. Nevertheless, they were also aggregable with another investigation [ 28 ]. The studies by Qin et al, also showed an early mtDNA release, which, however, did not peak until 12 h after surgery [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 69%
“…While the absolute plasma levels of mtDNA during cCPB were comparable with other studies investigating CABG patients, the kinetics differed from some studies [ 17 , 18 ]. Nevertheless, they were also aggregable with another investigation [ 28 ]. The studies by Qin et al, also showed an early mtDNA release, which, however, did not peak until 12 h after surgery [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 69%
“…In addition, (mildly) damaged mitochondria may be incorporated in exosomes, which translocate to the extracellular environment. Here, the mtDNA is released and end up in the circulation, forming cfc-mtDNA [42,43]. The presence of mitochondrial DNA in the media of rapid electrical-stimulated cardiomyocytes confirmed that mitochondrial DNA can be released out of the cardiomyocytes into the circulation.…”
Section: The Origin Of Cfc-mtdna In Serummentioning
confidence: 76%
“…Consistent with the protective role of EVs, EV DNA had a slightly higher copy number compared with cfDNA. A recent study also showed a higher concentration of mtDNA in EVs compared with plasma ( 37 ). The present study also confirmed that EV DNA covered the whole mitochondrial genome, suggesting that EV mtDNA can carry all the information from tumor cells and may be used as a potential cancer biomarker.…”
Section: Discussionmentioning
confidence: 93%